Axillary mechanical circulatory support improves renal function prior to heart transplantation in patients with chronic kidney disease - Ji-Min Jang; Tambi Jarmi; Basar Sareyyupoglu; Jose Nativi; Parag C. Patel; Juan C. Leoni; Kevin Landolfo; Si Pham; Daniel S. Yip; Rohan M. Goswami (Scientific Reports, 2023)
Abstract Impaired kidney function is often associated with acute decompensation of chronic heart failure and portends a poor prognosis. Unfortunately, current data have demonstrated worse survival in patients with acute kidney injury than in patients with chronic kidney disease during durable LVAD placement as bridge therapy. Furthermore, end-stage heart failure patients undergoing combined heart-kidney transplantation have poorer short- and long-term survival than heart transplants alone. We evaluated the kidney function recovery in our heart failure population awaiting heart transplantation at our institution, supported by temporary Mechanical Circulatory Support (tMCS) with Impella 5.5. The protocol (#22004000) was approved by the Mayo Clinic institutional review board, after which we performed a retrospective review of all patients with acute on chronic heart failure and kidney disease in patients considered for only heart and kidney combined organ transplant and supported by tMCS between January 2020 and February 2021. Hemodynamic and kidney function trends were recorded and analyzed before and after tMCS placement and transplantation. After placement of tMCS, we observed a trend towards improvement in creatinine, Fick cardiac index, mixed venous saturation, and glomerular filtration rate (GFR), which persisted through transplantation and discharge. The average duration of support with tMCS was 16.5 days before organ transplantation. The median pre-tMCS creatinine was 2.1 mg/dL (IQR 1.75–2.3). Median hematocrit at the time of tMCS placement was 32% (IQR 32–34), and the median estimated glomerular filtration rate was 34 mL/min/BSA (34–40). The median GFR improved to 44 mL/min/BSA (IQR 45–51), and serum creatinine improved to 1.5 mg/dL (1.5–1.8) after tMCS. Median discharge creatinine was 1.1 mg/dL (1.19–1.25) with a GFR of 72 (65–74). None of these six patients supported with tMCS required renal replacement therapy after heart transplantation. Early adoption of Impella 5.5 in this patient population resulted in renal recovery without needing renal replacement therapies or dual organ transplantation and should be further evaluated.